SYNTHESIS AND IN SILICO STUDY OF 4-AMINO-2,3,3,5-TETRASUBSTITUTED-2,3-DIHYDROISOTHIAZOLE-1-OXIDES - Chuchvera, Y.O.; Dobrydnev, A.V. (Reports of the National Academy of Sciences of Ukraine, 2024)
An efficient method for the synthesis of 4-amino-2-methyl-3,3-dialkyl-5-phenyl-2,3-dihydroisothiazole-1-oxides, including the ones with space-constrained spirocyclic substituents, has been developed. This class of compounds and in particular cyclic sulfinamides are considered as bioisosters of appropriately substituted lactams (cyclic amides). In silico studies and comparison of drug similarity parameters of model compounds showed that sulfinamide group (SO—N) is the closest equivalent of carboxamide group (CO—N) and can be considered as a new generation bioisosteric equivalent.